2020
DOI: 10.1155/2020/8108730
|View full text |Cite
|
Sign up to set email alerts
|

Proton Pump Inhibitor-Induced Galactorrhea in a Kidney Transplant Recipient: A Friend or Foe?

Abstract: Over the last decades, proton pump inhibitors (PPIs) have been widely used as the mainstay for treatment and prevention of gastrointestinal side effects, gastroesophageal reflux, and peptic ulcer disease. However, their safety profile has come into question recently after reports relating them to several side effects as well as kidney disease. Omeprazole, one of the mainly used PPIs, is almost entirely metabolized by the liver but the resulting metabolites are renally excreted. These metabolites may inhibit cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…There are reports of cases similar to the present one in recipients of kidney transplant who had elevated serum PRL levels at 140 ng/mL (2.8–29.2 ng/mL). Two weeks after stopping omeprazole, serum PRL levels returned to normal (18.8 ng/mL), accompanied by resolution of galactorrhea [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are reports of cases similar to the present one in recipients of kidney transplant who had elevated serum PRL levels at 140 ng/mL (2.8–29.2 ng/mL). Two weeks after stopping omeprazole, serum PRL levels returned to normal (18.8 ng/mL), accompanied by resolution of galactorrhea [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15] However, multiple case studies have been reported on the connection between PPIs and the development of hyperprolactinaemia with varying degrees of increase in serum prolactin levels when used either alone or in combination with prokinetics. [16][17][18][19][20][21] Some cohort studies have also reported a relative risk of developing sexual and reproductive outcomes, such as gynaecomastia, with the use of lansoprazole and omeprazole. 22,23 In addition, studies related to hormonal profiling with long-term use of PPI are lacking, and justify the need to conduct such a hormonal screening.…”
Section: Introductionmentioning
confidence: 99%